PENGARUH DISIPLIN BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS II SEKOLAH DASAR ISLAM AL-IKHLAS KECAMATAN KARANGREJO KABUPATEN TULUNGAGUNG - Duwi Febriyanti; Yasip (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by problems found in the learning process of Grade II students at Al-Ikhlas Islamic Elementary School. The playful nature of the students often disrupted classroom activities, resulting in an unconducive learning environment and low academic achievement. Therefore, it is necessary to instill learning discipline to help students follow rules and improve academic performance. This study aims to determine the effect of learning discipline on mathematics achievement and to explore the implementation of learning discipline among Grade II students at SDI Al-Ikhlas, Karangrejo Subdistrict, Tulungagung Regency. The research used a mixed methods approach with a concurrent embedded design, leaning more toward the quantitative side. Data were collected through observation sheet and tests. Quantitative data were analyzed using validity tests, reliability tests, normality tests, homogeneity tests, descriptive statistics, and t-tests. Qualitative data were analyzed using thematic analysis. The t-test results, processed using Jamovi 2.6.13, showed a significant improvement in students’ mathematics achievement after applying learning discipline, with a p-value < 0.001, thus Ha was accepted. Thematic analysis revealed six main themes in the implementation of learning discipline: time discipline, readiness and neatness in learning, focus and concentration, learning interest and motivation, activeness and participation, and academic responsibility. Therefore, it can be concluded that there is a significant effect of learning discipline on students’ mathematics achievement, with disciplined students performing better than those without structured learning habits.